Pendekatan Collaborative Action Research untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas II SDN 013832 Rahuning - Anjarwani, Ratih; Ritonga, Suci Ermalinda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to improve the mathematics learning outcomes of class II students at SDN 013832 Rahuning. This research is classroom action research (PTK) with the research subjects being class II students at SDN 013832 Rahuning. Data collection techniques through mathematics learning tests. This test consists of 20 multiple choice questions and 5 essay questions. Information is obtained through a desire to learn test and classroom observations. The research results showed that the Collaborative Action Research approach was effective in improving students' mathematics learning outcomes, and the average learning outcomes increased from 84.15 in Cycle I to 88.33 in Cycle II to 90.37 in Cycle III. In addition, the quality of students' work in group activities increases, as does student participation in learning.